The relationship between hearing loss and frailty in older adults at risk of cognitive decline: a cross-sectional study - Tian, Rong; Almeida, Osvaldo P.; Ford, Andrew H.; Flicker, Leon; Lautenschlager, Nicola T.; Robinson, Suzanne; Makate, Marshall; Pettigrew, Simone; Lee, Sin Huey; Dorsheimer, Ina; Yiannos, Jessica M.; Crawford, Libby; et al. (Frontiers in Aging, 2025)
ObjectivesTo investigate the association between hearing loss and frailty among a group of older community volunteers with mild cognitive impairment.DesignThis study recruited 162 older community volunteers who have mild cognitive impairment and symmetric age-related hearing loss. Participants’ hearing ability (including peripheral hearing, hearing handicap and central auditory processing) and frailty status were assessed and analysed. An independent t-test was conducted to compare hearing performance between frail and non-frail groups.ResultsThere were statistically significant differences between frail and non-frail groups for speech frequency hearing threshold, overall central auditory processing score and hearing handicap score, but not for high frequency hearing threshold.ConclusionFrail individuals exhibit poorer performance in peripheral and central hearing assessments, as well as in self-reported hearing handicap. Future randomised controlled trials are necessary to find out if the correction of hearing loss decreases the proportion of people affected by frailty in later life.